THE REVIEW OF PHYSIOTHERAPY ROLE IN CHILDREN WITH OBESITY - Sumal, Ravinder; Kaur, Inderpreet (International Journal of Psychosocial Rehabilitation, 2021)
In spite of global efforts to combat childhood obesity, the problem is still poorly understood and tough to treat. Because of their expertise in mobility and physical exercise, physiotherapists are well-suited to treat obese youngsters. However, the lack of physiotherapy-specific rules leaves their role ambiguous. Physiotherapists may use the findings of this scoping study to help them implement evidence-based practices in the treatment of paediatric obesity. Because of the continuous improvements in many obesity-related outcomes, physiotherapists should explore multicomponent methods and increasing physical activity in the treatment of obese children. Physiotherapists’ competence in physical activity prescription for the therapy of paediatric obesity is well matched to such techniques. The effectiveness of motor skill treatments should be examined in future studies, as should the role of environmental alteration and parental participation in ensuring the success of such interventions.